2020
DOI: 10.3390/su12114409
|View full text |Cite
|
Sign up to set email alerts
|

Types of Behavior of Flood Victims around Floodwaters. Correlation with Situational and Demographic Factors

Abstract: Recently, human behavior around floodwaters has been acknowledged as one of the factors that influence the risk of fatal incidents. The present study analyzes the behavior of flood victims by developing a systematic classification of their actions at the time of the flood. Based on this taxonomy, the study examines a flood fatality database for Greece (1960–2019) to quantify the different types of behavior and to examine potential correlations with various demographical and situational factors. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(152 reference statements)
0
7
0
1
Order By: Relevance
“…However, this percentage is expected to be very limited given the very consistent results on the TPB's ability to predict behavioral intention. Besides, previous research on flood mortality has shown that only a very small number of fatalities are caused by individuals who are motivated by something that would be considered an emergency (e.g., rescuing someone or something and others) [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this percentage is expected to be very limited given the very consistent results on the TPB's ability to predict behavioral intention. Besides, previous research on flood mortality has shown that only a very small number of fatalities are caused by individuals who are motivated by something that would be considered an emergency (e.g., rescuing someone or something and others) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Risk perception as a subjective assessment of the likelihood of personal and material damage has been suggested to contribute to the predictive ability of the TPB [16], although its association with behaviors against flood risks is still debated [36][37][38]. Among the demographic variables commonly used to complement analyses based on behavioral models, age and gender have been associated with drivers' intention to enter or avoid floodwaters [12,20,39,40], although not consistently [41].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini mengisyaratkan bahwa kondisi lingkungan dan tempat tinggal dari korban memiliki peran penting dalam menjamin keselamatan dari korban pada saat banjir terjadi. Selain itu menurut (Diakakis, 2020), terdapat beberapa faktor yang berpengaruh terhadap ada tidaknya kematian pada saat bencana banjir, antara lain sebagai berikut: ciri-ciri demografis korban, yaitu karakteristik yang membedakan masyarakat berdasarkan faktor-faktor demografis seperti umur, jenis kelamin, pendidikan dsb; lingkungan sekitar berupa kondisi lingkungan dari tempat banjir terjadi seperti perkampungan atau perumahan; keadaan saat terjadi banjir menjelaskan keberadaan korban pada saat banjir terjadi misalnya korban sedang berada di luar atau di dalam ruangan; aktivitas korban pada saat terjadinya banjir; serta waktu terjadinya banjir. Diantara kelima faktor tersebut, faktor demografis dan kondisi lingkungan merupakan faktor yang dapat dihitung dan dikontrol secara agregat.…”
Section: Pendahuluanunclassified
“…For the age group of 40-49 and 70-79, the numbers of male victims are more than twice that of females. In general, victims of flood incidents characterized by active behaviors were, on average, younger by a significant margin than the ones that perish exhibiting a passive behavior [34]. Storm Data provided information on the ages of individuals involved in 382 (67%) of the vehiclerelated flood fatalities.…”
Section: Demographics Of the Victimsmentioning
confidence: 99%